THE EFFECT OF GOAT CAGE FERTILIZER DOSAGE ON RESULTS OF THREE VARIETIES OF SESALE PLANT (Sesame indicum L.) - Awaludin Sinur Kholis; Dewi Ratna Nurhayatidan; Sartono Joko Santosa (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Effect of dose of goat manure on yield of several varieties of sesame (Sesamum indicum L.). Thisresearch was conducted in Wonoharjo Village, Kemusu District, Boyolali Regency on November 5, 2021until February 13, 2022. The purpose of this study was to determine the effect of goat manure dosageon the growth and yield of three varieties of sesame (Sesamum indicum L.). This study used a CompletelyRandomized Block Design (RAKL) which was arranged in a Split Plot consisting of 3 replications. Thetreatment was as follows: The first factor was 3 types of sesame varieties, namely Sbr 1, Winas 1 andWinas 2 varieties, the second factor was giving goat manure doses of 240 g / plant (D3), 180 g / plant(D2), 120 g / plant (D1), and without goat manure (D0), the design obtained 12 treatment combinations.Observational data were analyzed using Analysis of Variety (Anova) and further tested with the HonestSignificant Difference Test (BNJ) at the 5% level. The results showed that the application of goat manurewith a dose of 10 tons/ha (240 g/plant) gave the best results on the Winas 1 (V2) Sesame Variety.Keyword : Sesame, varieties, organic fertilizer